Current recommendations for the atopic dermatitis and food allergy treatment in children - S.L. Nyankovskyy; О.S. Nyankovska; M.S. Yatsula; M.I. Horodylovska (Zdorovʹe Rebenka, 2021)
Atopic dermatitis is the most common chronic childhood inflammatory skin disease. The chronic and recurrent nature of pediatric atopic dermatitis requires the use of active therapy for flares and maintenance therapy to promote the integrity of the skin barrier and prevent future flares. Systemic therapy is warranted for patients who have inadequate disease control (persistent severity and extent or significant impact on the quality of life) despite appropriate treatment with topical therapy and/or phototherapy. Over the past several decades, the prevalence of food allergy has continued to increase. It has become a significant health burden affecting 6–13% of the global population. There are two main types of medications that can be used to relieve the symptoms of the allergic reaction to food: antihistamines and adrenaline. Antihistamines can be used for food allergy prevention and treatment, in particular dimetindene maleate — Edermik.